The Role and Function of Religious Education and Religious Anthropology In Overcoming Mental Health Issues - Rahmatillaili, Fauziyyah Imma; Az Zahra, Fatimah (Riwayat: Educational Journal of History and Humanities, 2024)
Religious education and religious anthropology are the basis and concept of efforts in overcoming life problems, especially issues of human mental life. Mental health issues include the number of employees in government and private companies who experience mental health, the need for religious education and religious anthropology in understanding mental health issues, the many understandings of mental health issues that are actually experienced by everyone but have not found a way out or solution. The purpose of the study is to analyze the role of religious education and religious anthropology in influencing a persons good and bad mental health. Help cure someone who has mental health problems, find out the level of faith that has a positive impact on a persons mental health, and test the success of the influence of religious education and religious anthropology in helping someone overcome mental health problems. The research method used in this paper is qualitative, with a library research approach. The method with a literature study approach was chosen to make it easier for the author to study and explain a problem according to the theories of experts by referring to relevant arguments regarding the role and function of Religious Education and Religious anthropology in overcoming mental health issues. The results of the discussion state that religious education and religious anthropology function as a vehicle to emphasize respect for diversity and understand differences in religion and worldview. Religious education beliefs and practices contribute greatly to developing personal morality and sound judgment, influencing decisions that shape ones life. Positive religious coping seeks social support through religious leaders and congregations and reframes stressful events as connected to God.